Integration of Naqli and Aqli in microbiology teaching: Sharing the experience - Mohamed N.A.; Shahida W.; Ismail Z.; Isahak I.; Alias N.; Anuar Sani (International Islamic University Malaysia, 2024)
Background: In line with Universiti Sains Islam Malaysia's (USIM) tagline 'Exploring Islamic Science, Spearheading Knowledge', we embarked on a new paradigm of teaching by integrating naqli components into the microbiology and immunology curriculum. The main objective of this integration was to enhance students' appreciation towards Islam and Science, so that they would become good Muslim doctors. The naqli components were delivered through various teaching and learning techniques such as lectures, seminars, and online assignments. Methods: A total of eighty year 3 students from Faculty of Medicine and Health Sciences, USIM were involved in this study. They were exposed to the new method of teaching for the whole academic year, session 2014/2015. The effectiveness of this program was evaluated through questionnaires, given at the end of academic session. Outcome: More than 90% students agreed that the integration were clearly delivered, relevant to the topics at hand and enhanced their knowledge. Most students (> 90%) preferred interactive lectures rather than students' initiated method such as seminar and speaker's corner. About two third of the students did not prefer online method. Moreover, 15.9% of them said the allotted time was insufficient and 46% agreed that there was inadequate resources in the library. Conclusions: The integration of naqli components into microbiology subject was favoured by students. However, it should be improved with allocation of more slots, upgrading of online system and increment of relevant library resources. Looking forward, we are convinced this is the way to go in producing holistic doctors equipped with necessary knowledge, both in aqli and naqli to further advance Medicine and Islam.